Analisis Kinerja Keuangan Pemerintah Daerah Dan Pengaruh Pendapatan Asli Daerah, Dana Perimbangan, Dan Sisa Lebih Pembiayaan Anggaran Terhadap Belanja Modal - Az-zhara Shatila; Sri Rahayu; Salman Jumaili (POLITEKNIK LP3I JAKARTA, 2023)
This study aims to determine the financial performance of the Districts/Cities Governments in Jambi Province with the Regional Financial Independence Ratio and the Degree of Regional Financial Decentralization. As well determine the effect of Original Local Government Revenue (PAD), Balancing Funds and Financing Surplus on the Capital Expenditure in Districts/Cities in Jambi Province. This study is a quantitative descriptive research and quantitative research. The data used in this study is quantitative data with documentation techniques. The sample for this research is 11 districts/cities in Jambi Province on the official website of the Directorate General of Fiscal Balance. This study uses the Descriptive Analysis Method using ratios was used to financial performance of the Districts/Cities Governments in Jambi Province and Multiple Linear Regression Analysis with the help of SPSS version 25 was used to determine the effect of Original Local Government Revenue (PAD), Balancing Funds and Financing Surplus on the Capital Expenditure in Districts/Cities in Jambi Province. The results showed that the financial performance of the Districts/Cities Governments in Jambi Province, in terms of Regional Financial Independence Ratio, was categorized as very low and the Degree of Regional Financial Decentralization Ratio, it was categorized as very less. The results of testing the effect of PAD, Balance Fund and SILPA variables on Capital Expenditure show that PAD has no effect on Capital Expenditure, Balance Fund has no effect on Capital Expenditure, SILPA has an effect on Capital Expenditure.Keywords: Local Government Financial Performance, PAD, Balancing Fund, SILPA